Respuesta :

Answer:

x = 9

Step-by-step explanation:

Simplifying

17x + -12 = 114 + 3x

Reorder the terms:

-12 + 17x = 114 + 3x

Solving

-12 + 17x = 114 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.

-12 + 17x + -3x = 114 + 3x + -3x

Combine like terms: 17x + -3x = 14x

-12 + 14x = 114 + 3x + -3x

Combine like terms: 3x + -3x = 0

-12 + 14x = 114 + 0

-12 + 14x = 114

Add '12' to each side of the equation.

-12 + 12 + 14x = 114 + 12

Combine like terms: -12 + 12 = 0

0 + 14x = 114 + 12

14x = 114 + 12

Combine like terms: 114 + 12 = 126

14x = 126

Divide each side by '14'.

x = 9

Simplifying

x = 9

Answer:

X = 9

Step-by-step explanation:

17x - 12 = 114 + 3x

- 3                    -3

14x - 12 = 114

+12            +12

14x = 126

/14       /14

x = 9